Women’s Issues in the Campaign of Incumbent’s Wife in the Regional Head Election - Titin Purwaningsih; Tri Hastuti Nur Rochimah; Arrisi Jorgi Sutan; Danang Kurniawan (Department of Government Studies Universitas Muhammadiyah Makassar, 2022)
The representation of women in politics aims to deputize their interests. The problem is whether a female regional head candidate is more committed to women’s interests and represents women’s aspirations. What issues are raised in the campaign of a female candidate? This study aims to analyze women’s issues promoted by a female candidate in the 2020 Bengkalis Regional Head Election. The argument for taking the case study in Bengkalis is that a female candidate being the incumbent’s wife won the Regional Head Election, even though her husband had committed corruption and was sentenced to prison. Political family nominations are often based on popularity and family name, not on the candidate’s quality. This study analyzed women’s issues in the Regional Head Election with qualitative, descriptive, and NVivo analyses. The data were collected by documenting news in the media and the vision and mission presented by the candidate pairs. By taking the case of women’s issues in the political, economic, public service, social and legal sectors, the study results unveiled that all actors involved in the campaign, whether candidates, success teams, society, and public figures, were interested in women’s issues. Women’s issues becoming a concern in the campaign encompassed women’s economic empowerment, social security, health services, education, and domestic and children violence. Meanwhile, sanitation and the environment were not the issues in the campaign. The findings of this study reinforce previous studies that female candidates tend to raise issues related to social policy and redistribution and women’s services in the domestic sector.